Indonesia’s Delimited Maritime Boundaries - Jayadi, Anbar (Indonesia Law Review, 2015)
In case of Indonesia’s geographical condition, it goes without saying that with great potentials come great responsibilities to manage. With an overall distance of more than 1900 km from east to west and nearly 80% of its area are sea regulating its borders especially maritime boundaries will not only affect the integrity of the nation but also protect its natural resources.